Gender differences and the correlation of environmental knowledge with sustainability awareness after ESD-PjBL implementation - Heru Setiawan; K. Kusnadi; Hertien Koosbandiah Surtikanti; R. Riandi (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
Students' environmental knowledge and sustainability awareness are important competencies to prepare them to face global environmental challenges. The study aimed to evaluate the gender difference and correlation between students’ environmental knowledge, sustainability awareness, and sustainability practice frequency after Education for Sustainable Development (ESD) in Biology lesson. This study uses a quantitative research design with a one-group pretest posttest design using cognitive tests and a self-administered survey. The participants were year X students in one of the schools in Indonesia, during 2022/2023 academic year, including 114 students (M=54, F=60). The result found that although Indonesian high school students generally have high overall environmental knowledge students have low knowledge of global warming. Students have a high sustainability awareness and a high average frequency of practicing sustainability. Secondly, this research found that gender differences exist where female has significantly higher environmental knowledge than male students. Female students also have higher consciousness in all specific domains of sustainability, and they have statistically higher sustainability behavior than males. Environmental knowledge has a statistically moderately positive correlation with the frequency of sustainability practices. Environmental knowledge has a weak correlation with sustainability awareness. The frequency of sustainability practices has low correlation with sustainability awareness.